The application of cy-pres doctrine in the Malaysian law of charity / Ibrahim Hashim - Hashim, Ibrahim (Faculty of Law, 1985)
Since time immemorial Charities have played a positive role in society. Charities encourage private philanthrophy and the public receive various forms of return from the voluntary contribution. Besides that, charities harness talent, time and kindness of the people with different skills and sensitivity then would be possible. But unfortunately, the law being what it is has not been able to respond adequately. The writer is of the opinion that only by legislation canan effective and orderly development of law of charity and doctrine of cy-pres be achieved. The aim of this paper therefore is manifold, viz:(i) to study the existing corpus juris directly relatingto the law of charity particularly, cy-pres,(ii) to evaluate the court's decisions in the context of local setting,(iii) to make several case-studies of cy-pres doctrine in trust deed incorporation, and(iv) to make statutory recommendation.